Twenty years of change in a southeast Florida Acropora cervicornis thicket - Perez, Daniel M.; Jones, Nicholas P.; Goergen, Elizabeth A.; Gilliam, David S. (Frontiers in Marine Science, 2025)
Acropora cervicornis historically exists in large, dense thickets that provide a functionally unique habitat. However, populations in the Caribbean have declined by up to 98%, frequently isolating extant colonies. Remnant thickets are valuable research areas as they provide opportunities to assess community dynamics, resilience, succession, and the response to disturbances. BCA (Broward County Acropora) is a 10,000-m2A. cervicornis thicket located offshore Broward County in the Southeast Florida Coral Reef Ecosystem Conservation Area (Coral ECA), which has been monitored since 2003. The objective of this study was to analyze temporal changes in the thicket, specifically assessing the impact of disturbances and community dynamics that corresponded with fluctuations in the ratio between living and dead A. cervicornis. Photographic data were collected along 12 permanent transects to assess temporal changes in the percent benthic cover from 2003 to 2022. Demographic data on non-A. cervicornis corals were collected along four belt transects from 2012 to 2022. Live A. cervicornis cover declined from 34.8% ± 2% SE in 2003 to 2.4% ± 0.6% SE in 2022. The most severe declines corresponded with heat stress events and two hurricanes in 2005; a cold stress event in 2010; and heat stress, disease, and predation outbreaks between 2014 and 2016. As A. cervicornis died, other taxa utilized the remaining dead structure, with increases in the encrusting, weedy coral species Agaricia agaricites and the macroalgal and crustose coralline algal cover. However, the structural decline in later years suggests complete loss of this unique and complex habitat in the coming years. Thicket recovery will likely require active restoration and a reduction in local and global stressors.